Doença vestibular central por infarto isquêmico secundário a hipotireoidismo em cão - Chaves, Rafael Oliveira; Schwab, Marcelo Luis; Ripplinger, Angel; Copat, Bruna; Aiello, Graciane; Ferrarin, Denis Antonio; Flores, Mariana Martins; Fighera, Rafael; Mazzanti, Alexandre (Acta Scientiae Veterinariae, 2017)
Background: Hypothyroidism in dogs can cause lethargy, weight gain, dermatological signs and, uncommonly, neurological signs. These may involve the peripheral or central nervous system, leading to a decreased level of consciousness, central or peripheral vestibular disease, epileptic seizures, cognitive dysfunction, facial nerve paralysis, laryngeal paralysis, and polyneuropathy. There are few cases reported in the literature relating hypothyroidism and central vestibular disease. The aim of this study was to report a case of a stroke secondary to hypothyroidism that resulted in central vestibular syndrome in a dog. Case: A 13-year-old female Pitbull, weighting 37 kg, was referred to a Veterinary University Hospital with a two weeks history of dyspnea, coughing and walking difficulty. On neurological examination, the animal presented vertical nystagmus, somnolence, non-ambulatory tetraparesis, decreased postural reaction in all limbs and normal spinal reflexes. The laboratory exams revealed a mild leukocytosis and increased creatinine, glucose, cholesterol and triglycerides levels. Due to historical, clinical, neurological and laboratory tests findings, the animal was diagnosed with central vestibular syndrome secondary to an intracranial neoplasm. Clinical treatment was instituted with corticosteroids, however the animal did not respond and died. On necropsy, the heart was enlarged and coronary arteries were thicker. No macroscopic changes were found in the brain. On histological analysis, the coronary arteries were congest by lipids that almost occluded the arterial lumen. The same alteration were found in splenic and renal arterioles, and in the brain’s leptomeninges. Also in the brain, it was observed perivascular infiltration of mononuclear cells and focal gliosis. The thyroid was atrophied and fibrosed bilaterally. Therefore, those changes were compatible with atherosclerosis secondary to hypothyroidism. Discussion: Neurological sings secondary to hypothyroidism are uncommon. From 116 dogs with hypothyroidism, only 22 (19%) had neurological presentations. The majority was associated with peripheral nervous system showing polyneuropathy and cranial nerve dysfunction. When associated with central nervous system the most common sings are pathological nystagmus, postural reaction deficits, tetraparesis, hemiparesis, and paradoxical vestibular diseases. These signs are similar to the findings in the case reported here, characterizing it as a central vestibular disease. Different from humans, dogs have a natural resistance against atherosclerosis, however, hypothyroidism can result in lipids metabolic deficits, increasing its plasma levels. In this report, the arterial lesion and ischemia secondary to atherosclerosis, especially in the brain steam, have led to the neurological presentation. The dog also had hypercholesterolemia and hypertriglyceridemia, which are related to hypothyroidism. As high levels of cholesterol and triglycerides are common findings in hypothyroidism, it is important to evaluating blood levels of those lipids in dogs with central vestibular diseases, even though there are no others endocrinal signs. This case shows that, even though central vestibular disease is not a common neurological presentation in hypothyroidism, it is always important to considerer this metabolic affection as a precursor and a differential diagnosis to central vestibular disease.